2019
DOI: 10.1016/j.scijus.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The importance of dark adaptation for forensic examinations; an evaluation of the Crime-lite Eye™

Abstract: Forensic practitioners are recommended to dark adapt their eyes prior to conducting evidential searches in the dark. The dark adaptation process remains poorly standardised across the discipline, with little quantified regarding the benefits of such preparative steps. Herein, we report the findings of a study that recruited 50 participants to assess the effectiveness of the Crime-lite Eye™, a darkness adaptation device developed to assist forensic practitioners both in the laboratory and in field. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This work suggested that up to 16 % more evidence could be located after dark adapting the eyes for as little as 10 minutes prior to looking for fluorescent evidence in the dark. [4] This shows that alongside providing standardised fingermarks for research purposes, inkjet printing of amino acids can be used to provide standardised fluorescent marks when using a fluorescent fingermark development reagent such as DFO, or 1,2-indanedione. The use of two different concentrations of alanine solution allowed there to be some shapes which appeared brighter and were therefore easier to visualise, than some of the shapes printed in the lower concentration of alanine, which appeared less intense and were therefore harder to visualise, particularly prior to dark adaptation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work suggested that up to 16 % more evidence could be located after dark adapting the eyes for as little as 10 minutes prior to looking for fluorescent evidence in the dark. [4] This shows that alongside providing standardised fingermarks for research purposes, inkjet printing of amino acids can be used to provide standardised fluorescent marks when using a fluorescent fingermark development reagent such as DFO, or 1,2-indanedione. The use of two different concentrations of alanine solution allowed there to be some shapes which appeared brighter and were therefore easier to visualise, than some of the shapes printed in the lower concentration of alanine, which appeared less intense and were therefore harder to visualise, particularly prior to dark adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…[2] In order to find the most evidence possible, forensic examiners are advised to dark adapt their eyes prior to looking for fluorescent evidence in the dark, [3] and allowing the eyes to dark adapt for only 10 minutes has shown to improve the amount of evidence discoverable by 16 %. [4] To obtain these results, the method of printing artificial fingermarks was utilised, providing a standardised fluorescent test. The method for testing inkjet printing of amino acids using a standard inkjet printer and developing the printed patterns using both DFO as a fluorescent reagent, and ninhydrin is explained below.…”
Section: Introductionmentioning
confidence: 99%
“…Designed to help forensic practitioners, this system has, for example, recently been shown to benefit crime scene examiners' perception of fluorescent evidence. 9 Docosahexaenoic acid (DHA, Fig.1), a long chain omega-3 polyunsaturated fatty acid, is known to be present in high concentrations in some human tissues. 7 Retinal cells are an example of such a cell type, and the high levels of DHA found in these cells suggest that DHA plays an important role within the retina .…”
Section: Introductionmentioning
confidence: 99%
“…Designed to help forensic practitioners, this system has, for example, recently been shown to benefit crime scene examiners' perception of fluorescent evidence. 9 Docosahexaenoic acid (DHA, Fig. 1), a long chain omega-3 polyunsaturated fatty acid, is known to be present in high concentrations in some human tissues.…”
Section: Introductionmentioning
confidence: 99%